Dyslipidemia 2019
DOI: 10.5772/intechopen.87439
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Complexities in Dyslipidemias

Abstract: Adipose tissue is the largest organ in the human body and, in excess, contributes to dyslipidemias and the dysregulation of other vascular and metabolic processes. Adipose tissue is heterogeneous, comprised of several cell types based on morphology, cellular age, and endocrine and paracrine function. Adipose tissue depots are also regional, primarily due to sex differences and genetic variation. Adipose tissue is also characterized as subcutaneous vs. visceral. In addition, fatty deposits exist outside of adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 118 publications
0
2
0
Order By: Relevance
“…Recent studies have uncovered an additional role for BAT as an endocrine organ [33]. Brown adipose tissue secretes several molecules, which are collectively termed batokines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have uncovered an additional role for BAT as an endocrine organ [33]. Brown adipose tissue secretes several molecules, which are collectively termed batokines.…”
mentioning
confidence: 99%
“…Indeed, studies using transplantation of BAT in rodents have shown beneficial effects on metabolism and cardiovascular outcomes, which can be explained by the release of these endocrine factors into the circulation. For instance, BAT transplantation reversed the glycemic symptoms of two different models of type 1 diabetes without a change in insulin levels [33,34]. These batokines may alter metabolism by autocrine, paracrine, and endocrine mechanisms, thus modifying BAT itself or acting remotely on other organs.…”
mentioning
confidence: 99%